Popular participation and Previous County Health Conference - Luís Carlos Lopes-Júnior; Maria José Bistafa Pereira; Silvana Martins Mishima (Rev Rene)
The article aimed at reporting the participation of a post graduate nursing student in the core of a previous county health conference. This is an experience, descriptive and reflective report, held in Ribeirão Preto, São Paulo, Brazil, in the first semester of 2011. The Pre-Conference has resulted in the compilation of 50 proposals that involved the following areas: access to actions and health services; work management and health education; community participation; social security system; access and quality of reception. The Pre-Conference revealed the increasing plurality of society and its interests, and the distance between the managers on one hand, and on the other the organs of social participation.